Expansion of the Na3MIII(Ln/An)6F30 Series: Incorporation of Plutonium into a Highly Robust and Stable Framework. Issue 57 (17th September 2020) - Pace, Kristen A.; Klepov, Vladislav V.; Deason, Travis K.; Smith, Mark D.; Ayer, Gyanendra B.; Diprete, David P.; Amoroso, Jake W.; zur Loye, Hans‐Conrad
Abstract: Na n MAn6 F30 is an extremely versatile framework structure for incorporating tetravalent actinides (An) and cerium along with divalent or trivalent d‐metals (M); moreover, the structure exhibits a high resistance to harsh chemical conditions. This extreme robustness can potentially be exploited for the sequestration of plutonium in a stable matrix; however, no Na n MPu6 F30 compounds have been reported so far. Herein, we present four new plutonium fluorides that have been prepared as single crystals by mild hydrothermal synthesis methods. Structural characterizations revealed their compositions to be Na3 AlPu6 F30, Na3 FePu6 F30, Na3 CoPu6 F30, and Na2.4 Mn1.6 Pu6 F30 . Surprisingly, in the plutonium series, it was found that Co 2+ and Mn 2+ precursors oxidized to form Na3 Co III Pu6 F30 and Na2.4 Mn II/III 1.6 Pu6 F30, whereas the analogous reactions for cerium result in reduction of the transition metal, even when beginning with a M 3+ precursor. While cerium is often used as a surrogate for plutonium, this work serves as an example that deviations between their chemistries do occur. Abstract : Striking a balance : The ability to synthesize novel plutonium compounds of the Na n MPu6 F30 compositional type was found to be strongly dependent upon a delicate balance between the size limitations of the structure and the Pu 4+ and M 2+ /M 3+ redox chemistry.